2015
DOI: 10.1200/jco.2014.60.6376
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Cure of All Children With Cancer Through Collaborative Efforts: Pediatric Oncology As a Global Challenge

Abstract: Advances in the treatment of childhood cancers have resulted in part from the development of national and international collaborative initiatives that have defined biologic determinants and generated risk-adapted therapies that maximize cure while minimizing acute and long-term effects. Currently, more than 80% of children with cancer who are treated with modern multidisciplinary treatments in developed countries are cured; however, of the approximately 160,000 children and adolescents who are diagnosed with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
374
2
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 341 publications
(400 citation statements)
references
References 55 publications
3
374
2
21
Order By: Relevance
“…This ratio of childhood leukemia is least found in southern Africa (0.5%), Caribbean (0.5%) and Oceania (0.6%) in total world cases. Frequencies of childhood leukemia in another region of globe were in Europe 9.9%, Central America 2.9%, South America 7.3%, Northern western Africa 5.1%, south eastern Asia 9.6% and western Asia [15]. Al-Mutlaq et al in 2015 study result revealed that 8% childhood cancer accounted in total malignancy cases.…”
Section: Discussionmentioning
confidence: 97%
“…This ratio of childhood leukemia is least found in southern Africa (0.5%), Caribbean (0.5%) and Oceania (0.6%) in total world cases. Frequencies of childhood leukemia in another region of globe were in Europe 9.9%, Central America 2.9%, South America 7.3%, Northern western Africa 5.1%, south eastern Asia 9.6% and western Asia [15]. Al-Mutlaq et al in 2015 study result revealed that 8% childhood cancer accounted in total malignancy cases.…”
Section: Discussionmentioning
confidence: 97%
“…As such, there needs to be much more attention paid to this public health burden. In terms of childhood cancer specifically, the survival rate has dramatically increased over time in developed countries, while it remains low in low- and middle-income countries due to economic, genetic, and environmental factors [2]. With progress in science and technology, there have been unprecedented advances in the diagnosis and treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This process is important; most children with cancer live in LMICs and supportive care is at least as important in these centers as in HICs [16]. We present our experience in order to help others who plan to adapt CPGs for LMIC utilization.…”
Section: Discussionmentioning
confidence: 99%